2019
DOI: 10.1186/s40246-019-0249-8
|View full text |Cite
|
Sign up to set email alerts
|

Human genetics and genomics research in Ecuador: historical survey, current state, and future directions

Abstract: BackgroundIn South America, the history of human genetics is extensive and its beginnings go back to the onset of the twentieth century. In Ecuador, the historical record of human genetics and genomics research is limited. In this context, our work analyzes the current status and historical panorama of these fields, based on bibliographic searches in Scopus, Google Scholar, PubMed, and Web of Science.ResultsOur results determined that the oldest paper in human genetics coauthored by an Ecuadorian institution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Our findings resonate with previous studies by Eum et al ( 43), Cheung et al (44), and Abdul Rahim et al (45), which similarly reported low levels of trust in research institutions among survey participants. Several factors contribute to this distrust and reluctance to contribute genetic material, including suspicions of political or economic interests influencing genetic studies, concerns regarding the privacy of genetic data, limited human resources and expertise in genetics, inadequate technological infrastructure for genetic and biomedical testing, and high costs associated with genetic tests.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings resonate with previous studies by Eum et al ( 43), Cheung et al (44), and Abdul Rahim et al (45), which similarly reported low levels of trust in research institutions among survey participants. Several factors contribute to this distrust and reluctance to contribute genetic material, including suspicions of political or economic interests influencing genetic studies, concerns regarding the privacy of genetic data, limited human resources and expertise in genetics, inadequate technological infrastructure for genetic and biomedical testing, and high costs associated with genetic tests.…”
Section: Discussionsupporting
confidence: 92%
“…Although research output in genomics and bioinformatics has significantly increased in the last decade in Latin America, impact and quality is still a matter of concern. A comparative analysis of the data presented here with similar initiatives in other Latin American countries (Blas et al, 2011;Bicudo, 2016;De Las Rivas et al, 2019;Zambrano-Mila et al, 2019;Armenta-Medina et al, 2020) has revealed some interesting patterns. One of them is the recognition for a better characterization of the genetic structure of the region's population, a theme that can be deeply explored by genomics and bioinformatics.…”
Section: Discussionmentioning
confidence: 62%
“…Several factors contribute to this distrust and reluctance to contribute genetic material, including suspicions of political or economic interests influencing genetic studies, concerns regarding the privacy of genetic data, limited human resources and expertise in genetics, inadequate technological infrastructure for genetic and biomedical testing, and high costs associated with genetic tests. Despite these challenges, our findings suggest promising prospects for the study and research of human genetics in Ecuador ( 46 ).…”
Section: Discussionmentioning
confidence: 93%